Risk factors that potentiate weaknesses in institutionalized elderly (Research, Society and Development, 2020)
The article aims to analyze risk factors that increase weaknesses in residents of Long-Term Care Institutions for the Elderly. The study is characterized as an integrative literature review that consisted of six stages: definition of the theme and formulation of the guiding question; establishment of inclusion and exclusion criteria; definition of descriptors; pre-selection of articles; evaluation of selected studies; and presentation of the review. Sixteen studies were reviewed, between the years 2016 to 2019, based on the search in the Scientific Electronic Library Online (Scielo), LILACS and Pubmed databases using as descriptors Elderly, Long Term Care Institution for the Elderly, frailty, malnutrition, depression, accidents due to falls. According to evidence from these studies, depression stands out among the risk factors that increase weaknesses in institutionalized elderly people, which may be associated with the institutionalization time, self-perceived health and quality of sleep. There was also a prevalence of malnutrition in this group of elderly people, as well as an increased risk of falls, which may be related to the individual's psychological health and impaired nutritional status. Such factors considerably affect the health condition and quality of life of this population. It appears that knowledge about the main risk factors that increase weaknesses in institutionalized elderly people is of paramount importance for the application of preventive actions, aiming to preserve their health.